Good Governance, Komitmen Profesional dan Akuntabilitas Layanan Publik, Locus of Control Sebagai Intervening - Iro Jationo; Widarto Rachbini (Magister Akuntansi Universitas Pancasila, 2015)
A B S T R A C T This research aims to empirically examine the relationship between good governance and professional commitment to accountability of public service procurement of goods/services through the government’s locus of control as an intervening variable. The population in this research are all service personnel procurement of goods/services certified government spread across 42 SKPDs (working units) in Tangerang City Government which is responsible for the procurement of goods/services of the government, as many as 70 people. In this research, variables used consisted of the dependent variable accountability of public service procurement of goods/services of the government while the independent variable is good governance and professional commitment, and locus of control variable as an intervening variable. The results showed that the governance and professional commitments do not affect the accountability. locus of control significantly influence accountability. In this study, locus of control is not a variable pemediasi on accountability procurement of goods and services. A B S T R A K Penelitian ini bertujuan untuk menguji secara empiris hubungan antara tata kelola yang baik dan komitmen profesional terhadap akuntabilitas pengadaan pelayanan publik barang/jasa melalui locus of control pemerintahan sebagai variabel intervening. Populasi dalam penelitian ini adalah seluruh tenaga pelayanan pengadaan barang/jasa pemerintah bersertifikat yang tersebar di 42 SKPD (satuan kerja) di Pemerintah Kota Tangerang yang bertanggung jawab untuk pengadaan barang/jasa pemerintah, sebanyak 70 orang. Pada penelitian ini, variabel yang digunakan terdiri dari akuntabilitas pengadaan pelayanan publik barang/jasa pemerintah sebagai variabel dependen sedangkan variabel independen adalah tata kelola yang baik dan komitmen profesional, dan locus of control sebagai variabel intervening. Hasil penelitian menunjukkan bahwa tata kelola pemerintah dan komitmen profesional tidak berpengaruh terhadap akuntabilitas. Locus of control berpengaruh signifikan terhadap akuntabilitas. Pada penelitian ini, locus of control bukan merupakan variabel pemediasi pada akuntabilitas pengadaan barang dan jasa. JEL Classification: H53